2012
DOI: 10.4172/2161-1149.1000113
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Urate and Tumor Necrosis Factor-α Increase Apoptosis in Human Chondrocyte Cultures

Abstract: Monosodium urate and tumor necrosis factor-α, are two potent mediators of separate inflammatory response pathways in arthritic joints where inflammation may be accompanied by the loss of chondrocyte vitality via apoptosis. To address this possibility in vitro, chondrocyte cultures were employed to determine the extent to which monosodium urate and recombinant TNF-α altered the frequency of apoptotic chondrocytes. Apoptosis as a function of the activation of p38 kinase, C-Jun-terminal kinase, signal transducer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 39 publications
(59 reference statements)
0
37
0
Order By: Relevance
“…Thus, dysfunctional intracellular signaling induced by pro-inflammatory cytokines was shown to be responsible for aberrant immune-cell survival [31-33], articular chondrocyte apoptosis [33,34] and/or “apoptosis-resistance” of cells in RA synovial tissue [35-38]. Abnormalities in the aforementioned JAK/ STAT, SAPK/MAPK and PI-3K/AKT/mTOR pathways [26,27,39-41] as well as aberrant activities in spleen tyrosine kinase (Syk) [42-46], the sphingosine kinases, SphK1 and SphK2 [47-52], transforming growth factor β-activated kinase-1 (TAK1) [53], bone marrow kinase (BMX) [54] and nuclear factor-κB-inducing kinase (NIK) [55] have all been found in patients with active RA.…”
Section: Intracellular Signaling Regulates Immune-cell Synoviocyte Smentioning
confidence: 99%
“…Thus, dysfunctional intracellular signaling induced by pro-inflammatory cytokines was shown to be responsible for aberrant immune-cell survival [31-33], articular chondrocyte apoptosis [33,34] and/or “apoptosis-resistance” of cells in RA synovial tissue [35-38]. Abnormalities in the aforementioned JAK/ STAT, SAPK/MAPK and PI-3K/AKT/mTOR pathways [26,27,39-41] as well as aberrant activities in spleen tyrosine kinase (Syk) [42-46], the sphingosine kinases, SphK1 and SphK2 [47-52], transforming growth factor β-activated kinase-1 (TAK1) [53], bone marrow kinase (BMX) [54] and nuclear factor-κB-inducing kinase (NIK) [55] have all been found in patients with active RA.…”
Section: Intracellular Signaling Regulates Immune-cell Synoviocyte Smentioning
confidence: 99%
“…Our laboratory had previously shown that rhTNF-α was a potent pro-inflammatory cytokine inducer of apoptosis in human chondrocytes which had been enzymatically dissociated from OA knee cartilage [24]. This was indicated by the increased number of DAPI/TUNEL-positive chondrocytes in the rhTNF-α-treated group compared to a control group.…”
Section: Discussionmentioning
confidence: 99%
“…The number of apoptotic chondrocytes was determined by the 4', 6-DiAmidino-2-Phenyl/Indole/Terminal deoxynucleotidyl transferase dUTP Nick End Labeling (DAPI/TUNEL) assay as previously described [24]. C-28/I2 chondrocytes were incubated with either DMEM/F12 (1:1) plus 0.5% FBS, DMEM/F12 (1:1) plus 10% FBS, DMEM/F12 (1:1) plus DMSO and 0.5% FBS, or rhTNF-α (20 ng/ml), rhIL-6 (50 ng/ml), or rhOSM (50 ng/ml) or various combinations of rhTNF-α (20 ng/ml) and U0126 (10 μM), rhIL-6 (50 ng/ml) and U0126 (10 μM), rhIL-6 plus tocilizumab (200 ng/ml) or rhOSM (50 ng/ml) which were all maintained in DMEM/F12 (1:1) plus 0.5% FBS for 24 hr.…”
Section: Methodsmentioning
confidence: 99%
“…We employed the 30 min time point for analysis of STAT1 protein activation based primarily on our previously published western blot data [47] which showed that activated STAT proteins accumulated in human chondrocyte protein lysate in response to tumor necrosis factor-α for up to 30 min after which time the anti-p-STAT band was undetectable by western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…Western blots were produced as previously described [47]. However, in this study we employed a sequential antibody-probing/stripping technique to measure either U-STAT1 or p-STAT1 after which the immunoblot was stripped and reprobed with the β-actin antibody.…”
Section: Methodsmentioning
confidence: 99%